1996
DOI: 10.1093/carcin/17.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Dual phenotypic expression of hepatocytes and bile ductular markers in developing and preneoplastic rat liver

Abstract: This study supports the existence of a pluripotent liver stem cell population which has the potential to differentiate into hepatocytes and bile ductular cells. We compared the expression of hepatocyte-specific and bile ductular-specific markers in fetal and preneoplastic rat liver. L-pyruvate kinase (L-PK) and alpha glutathione S-transferase (GST) were used as adult hepatocyte-specific markers, while cytokeratin 19 (CK19) was used as a bile ductular-specific marker. pi GST and M2-pyruvate kinase (M2-PK), whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 11 publications
4
39
0
3
Order By: Relevance
“…[73][74][75] Immunohistochemistry of BDL livers demonstrated that some bile ductular cells expressed Ptc and Gli-2, suggesting that relatively immature liver epithelial cells are Hh targets. Our in vitro studies support this concept because, under our culture conditions, the Ptc-( þ )ve cholangiocyte line coexpressed several oval cell markers, mpk and c-kit, [44][45][46][47] and the immature cholangiocyte marker, N-CAM, 3,43,76,77 as well as markers of more mature cholangiocytes (ie, aquaporin-1 and CK-19). If further research verifies that Hh signaling promotes the outgrowth of relatively immature liver epithelial cells, this might explain why patchy lobular necrosis was worse in PtcLacZ mice than WT mice after BDL.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…[73][74][75] Immunohistochemistry of BDL livers demonstrated that some bile ductular cells expressed Ptc and Gli-2, suggesting that relatively immature liver epithelial cells are Hh targets. Our in vitro studies support this concept because, under our culture conditions, the Ptc-( þ )ve cholangiocyte line coexpressed several oval cell markers, mpk and c-kit, [44][45][46][47] and the immature cholangiocyte marker, N-CAM, 3,43,76,77 as well as markers of more mature cholangiocytes (ie, aquaporin-1 and CK-19). If further research verifies that Hh signaling promotes the outgrowth of relatively immature liver epithelial cells, this might explain why patchy lobular necrosis was worse in PtcLacZ mice than WT mice after BDL.…”
Section: Discussionsupporting
confidence: 66%
“…45 The latter transcripts were also demonstrated in oval cells, which are known to coexpress neural, smooth muscle and progenitor markers. [44][45][46][47] These data suggest that Hh pathway activity occurs in immature cholangiocytes (ie, bile ductular cells).…”
Section: Hh Signaling Increases After Bile Duct Ligationmentioning
confidence: 84%
“…More importantly, MPK staining is present in small hepatocytes, many of which also express the liver-specific isoenzyme of pyruvate kinase. 35 This finding suggests that A6 and MPK may distinguish oval cells that have differentiated along the bile duct and hepatocyte lineages, respectively. If this is correct, the finding that in IFN␥ KO mice only MPK ϩ oval cells are reduced suggests this cytokine affects the generation of hepatocytes, rather than bile duct cells, from oval cells.…”
Section: Discussionmentioning
confidence: 94%
“…It is our view that two distinct populations exist in rats fed a choline-deficient, ethionine-supplemented (CDE) diet, as detailed analysis of pyruvate kinase (PK) and GST isoenzyme expression reveals that most oval cells coexpress fetal and biliary specific markers, while a minor population coexpress fetal and adult hepatocyte markers. 9,10 Accordingly, oval cells are a multipotent cell population with the potential to differentiate into hepatocytes and biliary epithelia, and under certain conditions, pancreatic and intestinal epithelia (Fig. 1).…”
Section: Oval Cells Are a Heterogeneous Cell Compartmentmentioning
confidence: 99%